Perlindungan Hukum Bagi Nelayan Dalam Bagi Hasil Tangkap Ikan di Kabupaten Pohuwato : Tinjauan Syarat Sah Perjanjian - Abdul Rezal Antukai; Nirwan Junus; Melisa Towadi (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2024)
This journal discusses the legal requirements for fish catch as the object of a production sharing agreement in Pohuwato Regency. In the context of business cooperation between ship owners and crew members, production sharing agreements have become common practice, although they are often done verbally. This research aims to examine the legal requirements that must be fulfilled by fish catches in order to be the object of a valid production sharing agreement. In this research, normative research methods were used with a legislative approach, a case approach and a conceptual approach. The data used is secondary data obtained through literature study and analysis carried out qualitatively. The research results show that there are four legal conditions that must be fulfilled in an agreement, namely agreement between both parties, ability to carry out the agreement, clear and halal objects, and a form that complies with applicable legal provisions. Apart from that, it was also stated that Law Number 16 of 1964 concerning Fishery Profit Sharing provides an outline of the minimum percentage of profit sharing that must be received by fishermen. However, this research also reveals that the production sharing agreement system in Pohuwato Regency does not always work as it should, especially due to inhibiting factors such as low levels of education. Therefore, the legal protection of fishermen as parties entering into production sharing agreements needs to be improved. In conclusion, to fulfill the legal requirements for fish catch as the object of a production sharing agreement, there needs to be an agreement between both parties, fulfillment of applicable legal requirements, as well as adequate legal protection for fishermen as parties involved in the agreement. Efforts to increase legal understanding and awareness of fishermen's rights need to be made to ensure fairness in the distribution of fish catches in Pohuwato Regency.